PENERAPAN BIOSECURITY DAN PROTOKOL KESEHATAN PADA USAHA PETERNAKAN BABI RAS PERSILANGAN - Sumardani, N.L.G.; Budaarsa, K.; Puger, A.W.; Witariadi, N.M. (Buletin Udayana Mengabdi; Vol 23 No 6 (2024): Buletin Udayana MengabdiDO - 10.24843/BUM.2024.v23.i06.p05, 2024)
In the pig farming business, biosecurity is an effort to prevent the entry and spread of infectious diseases into and out of the farm environment. The most important thing from a biosecurity system is its implementation which is carried out thoroughly and continuously. Biosecurity does not have to be synonymous with large costs but can be applied according to requirements at a low cost. The research was conducted by purposive sampling method and centered in Taro Village Tegalalang District, Bali Province. There are two main observations, namely pig farms that apply biosecurity and do nit apply biosecurity. Variables observed include aspects of production and aspects of the reproductive performance of pigs. The results showed that the production and reproductive performance of pigs showed a significant difference (P<0,05) between the two observed farms management. The conclusion of this study is that the application of comprehensive and continuous biosecurity in the pig farming business really needs to be applied to increase the production and reproductive performance of pigs.